Digital Media Selection Strategy for Marketing Communication in Sabang City Tourism - Herman; Ade Irma; Fajri Chairawati (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Digital media offers great opportunities for tourism marketing communications, but choosing the right platform and understanding user interactions are still challenges. Although several studies have discussed digital media in tourism marketing, specific research on digital marketing communication strategies on social media platforms, as well as analysis of user interactions, is still limited, especially in the context of tourism promotion in Sabang City which has great potential but needs to increase tourist visits. This study uses a descriptive qualitative design. Data collection using in-depth interviews with the Head of Marketing at the Sabang City Tourism Office and the owner of Dear Sabang Travel, as well as documentation studies, to reveal the strategy for selecting digital media in tourism marketing communications in Sabang City. Data were analyzed using thematic analysis techniques, with source triangulation and member checking to ensure the validity and reliability of the findings. The findings of this study reveal that the strategy for selecting digital media in tourism marketing communications in Sabang City, which involved interviews with Mrs. Murdiana from the Tourism Office and Mr. Muhammad Fachrurrazi from Dear Sabang Travel, focuses on the use of social media platforms such as Instagram and TikTok. Both informants emphasized the effectiveness of social media in reaching young tourists, raising awareness, and engaging audiences. Collaboration with influencers and local travel to increase the visibility of Sabang City tourism, as well as the need for a more comprehensive evaluation of the effectiveness of the implemented digital marketing strategies.